Galantamine derivatives with indole moiety: Docking, design, synthesis and acetylcholinesterase inhibitory activity. Issue 17 (1st September 2015) - Atanasova, Mariyana; Stavrakov, Georgi; Philipova, Irena; Zheleva, Dimitrina; Yordanov, Nikola; Doytchinova, Irini
Graphical abstract: Abstract: The inhibitors of acetylcholinesterase are the main therapy against Alzheimer's disease. Among them, galantamine is the best tolerated and the most prescribed drug. In the present study, 41 galantamine derivatives with known acetylcholinesterase inhibitory activities expressed as IC50 were selected from the literature and docked into a recombinant human acetylcholinesterase by GOLD. A linear relationship between GoldScores and pIC50 values was found and used to design and predict novel galantamine derivatives with indole moiety in the side chain. The four best predicted compounds were synthesized and tested for inhibitory activity. All of them were between 11 and 95 times more active than galantamine. The novel galantamine derivatives with indole moiety have dual site binding to the enzyme—the galantamine moiety binds to the catalytic anionic site and the indole moiety binds to peripheral anionic site. Additionally, the indole moiety of one of the novel inhibitors binds in a region, close to the peripheral anionic site of the enzyme, where the Ω-loop of amyloid beta peptide adheres to acetylcholinesterase. This compound emerges as a promising lead compound for multi-target anti-Alzheimer therapy not only because of the strong inhibitory activity, but also because it is able to block the amyloid beta deposition on acetylcholinesterase.